Factor Analysis of Human Resource Practices in Nepalese Insurance Companies (The International Research Journal of Management Science, 2016)
This study is focused on the human resource practice is pertinent to all type of organizations, regardless of its nature, size and scope. Organization must ensure appropriate human resource practice to operate and succeed in the business. Employees’ from Nepalese insurance companies has been regarded as sample to explore the study on human resource practice. The result showed four factors prevailing in this sector.